KETIMPANGAN PENDAPATAN DAN POTENSI SEKTORAL DI KALIMANTAN TIMUR TAHUN 2002-2004 - Kusumaningrum, Mayahayati (Pusjar SKPP Lembaga Administrasi Negara, 2006)
One of common characteristics of the less-developed countries is widespread of economic inequality among their regions. The problem of regional disparity occurs due to differentiation of both quality and quantity of human and natural resources. Indonesia is a classic example of a country with deep economic gap among its provinces. Ironically, East Kalimantan as one of the richest provinces in Indonesia has experienced the similar case. The development of Cities is approximately faster than that of Districts. Such situation is contributed by some factors such as concentration of economic activities, uneven distribution of investment, mobility rate of production, deprived domestic and international trade, etc. The implementation of policy on regional autonomy is intended to minimize such development upheaval. To some extent, however, autonomy laws have been sharpening the disparity among regions, particularly between oil-and-gas-based-regions and non-oiland- gas-based-regions. It means that natural resource (i.e. oil and gas) industry plays crucial role in escalating local development, especially where third sector (services, technology-based, communication, etc) is poorly developed. In the long-term perspective, the dependency on natural resource which is nonrenewable should be shifted to other sector having the potency to be continuously renewed. By using affiliation from Location Quotient (LQ) analysis, this paper tries to excavate the potency and inequality of economic development in East Kalimantan Province. The analysis aims to identify the priority of sound development sector in certain area and finding out the area owning advantage of location from any sector, in order to improve efficiency of economic activities.Keywords: ketimpangan ekonomi/pendapatan, sektor potensial, Kalimantan Timur.